Den sande helt i Lykke-Per er Jakobe - Munk Rösing, Lilian (Pontoppidaniana, 2023)
Abstract Per Sidenius, obviously, is the protagonist of Lykke-Per (A Fortunate Man), Henrik Pontoppidan’s novel. The heroine of the novel is, no doubt, Jakobe, the Jewish lady Per is engaged to. In this article, Lilian Munk Rösing, focuses on the erotic attraction between the main characters of the novel. Jakobe is, at the same time, attracted and repelled by the brute, “butcher-like” Per. Per, on his side, is fascinated by the Jewish lady of the world. Munk Rösing argues that his complex character exposes Per as “empty”, where as her complex character makes Jakobe the attractive object of love, not easily grasped and simplified.